The search for novel analgesics: re-examining spinal cord circuits with new tools - Smith, Kelly M.; Madden, Jessica F.; Callister, Robert J.; Hughes, David I.; Graham, Brett A. (Frontiers in Pharmacology, 2014)
In this perspective, we propose the absence of detailed information regarding spinal cord circuits that process sensory information remains a major barrier to advancing analgesia. We highlight recent advances showing that functionally discrete populations of neurons in the spinal cord dorsal horn play distinct roles in processing sensory information. We then discuss new molecular, electrophysiological, and optogenetic techniques that can be employed to understand how dorsal horn circuits process tactile and nociceptive information. We believe this information can drive the development of entirely new classes of pharmacotherapies that target key elements in spinal circuits to selectively modify sensory function and blunt pain.